Leveraging Learners’ Metacognitive Activities for Recommendation in Technology Enhanced Learning Systems (Journal of Organizational Psychology, 2021)
There has been a growing interest in assisting learners develop control over their learning and behaviour. Metacognition — the ability to think about thinking — can be an effective learning strategy that encourages learners take control of their learning. Typically, while reading, learners engage in a number of metacognitive reading activities e.g. text marking, highlighting. This study examines the effectiveness of utilizing the metacognitive activities generated by learners as a preference elicitation method to guide the recommendation of personalized learning resources. Providing appropriate resources that facilitate personalized learning is considered imperative given that learning differs from one learner to another.
Keywords: organizational psychology; learners; metacognition; behaviour; metacognitive learning activities; personal recommender system; technology enhanced learning